2012
DOI: 10.1017/s0007114512004278
|View full text |Cite
|
Sign up to set email alerts
|

Tomato juice consumption reduces systemic inflammation in overweight and obese females

Abstract: Tomatoes are the richest source of lycopene, a potent antioxidant. Tomato products improve antioxidant defences and reduce the risk of inflammatory diseases, at least partly, due to the presence of lycopene. Lycopene, as an anti-inflammatory agent, prevents the production of inflammatory cytokines. Obesity is a chronic inflammatory condition in which the increased level of body fat leads to an increase in circulating inflammatory mediators. We hypothesised that the consumption of a lycopene-rich food would red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 27 publications
3
100
0
1
Order By: Relevance
“…An association between diet and inflammation has been consistently demonstrated in observational studies [21], intervention trials [22,23], and animal experiments [24]. In these studies, low-fat diet [22], fruit [25], tomatoes [23,26], nuts [27], whole grains [21,28], fish [29], and, especially, nutrients from foods rich in phytochemicals or antioxidants (e.g. carotene, lycopene, vitamin C, flavonoids [30][31][32]) have been found to have anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 93%
“…An association between diet and inflammation has been consistently demonstrated in observational studies [21], intervention trials [22,23], and animal experiments [24]. In these studies, low-fat diet [22], fruit [25], tomatoes [23,26], nuts [27], whole grains [21,28], fish [29], and, especially, nutrients from foods rich in phytochemicals or antioxidants (e.g. carotene, lycopene, vitamin C, flavonoids [30][31][32]) have been found to have anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, it has recently been demonstrated that tomato juice administration reduced flow-mediated vasodilation (FMD), which is a marker of endothelial function, in ultra-marathon runners (Samaras et al, 2014). In another study among obese patients, serum IL-6 concentration was decreased following lycopene administration (Ghavipour et al, 2013). A limiting effect of lycopene on adipose tissue pro-inflammatory cytokine and chemokine production has also been reported in mice, suggesting prevention or limitation of the prevalence of obesity-associated pathologies, such as insulin resistance (Gouranton et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…LDL oxidation is a key factor in the development and progression of atherosclerotic lesions. Paraoxinase (PON) has the ability to protect HDL and LDL oxidation (Ghavipour et al, 2013). A number of studies have shown that tomato products favorably affect lipid metabolism (Ali and Agha, 2009;Fuhran et al, 1997;Navarro-GonzĂĄlez et al, 2014;Sesso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, reduced serum IL-6 levels, but not IL-8 or TNF-α levels, were recorded in a group of 10 obese female university students (compared to 9 controls) after ingesting 330 mL/day of tomato juice every day for 20 days [57]. This effect was attributed to the anti-inflammatory effects of the lycopene in the tomato juice [56], which reduces the translocation of NF-kB and in turn the reduced expression of inflammatory biomarkers, including IL-8 and TNF-α [57]. According to these authors, the anti-inïŹ‚ammatory effects attributed to lycopene could be influenced by the presence of ÎČ-carotene and vitamin C in the tomato juice because these nutrients have been shown to decrease inïŹ‚ammation via their probable redox-based effect on the inactivation of NF-kB.…”
Section: Discussionmentioning
confidence: 81%